2020
DOI: 10.1039/d0nr04098c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the synthesis of polymetallic-doped ZIF derived materials for efficient hydrogenation of furfural to furfuryl alcohol

Abstract: Cu, Co and Zn modified N-doped porous carbons (CuCo/Zn@NPC) are prepared using a polymetallic homogeneous doping and self-templating method as high performance non-noble metal catalysts for the hydrogenation of furfural...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…, reaction temperature) for hydrogenation and transfer hydrogenation of furfural over Cu-, Ni-, Co-, and Fe-based non-noble metal catalysts are comparable (entries 3 and 4 in Table 1), and the selectivity of CTH is relatively higher. 31–35 Notably, various Lewis acid–base catalysts, which are inefficient or even incapable of catalyzing hydrogenation involving H 2 , have shown excellent CTH performance under quite mild conditions (entries 5 and 6 in Table 1). Catalyst design and exploration in this area have been hot topics in the last months.…”
Section: Introductionmentioning
confidence: 99%
“…, reaction temperature) for hydrogenation and transfer hydrogenation of furfural over Cu-, Ni-, Co-, and Fe-based non-noble metal catalysts are comparable (entries 3 and 4 in Table 1), and the selectivity of CTH is relatively higher. 31–35 Notably, various Lewis acid–base catalysts, which are inefficient or even incapable of catalyzing hydrogenation involving H 2 , have shown excellent CTH performance under quite mild conditions (entries 5 and 6 in Table 1). Catalyst design and exploration in this area have been hot topics in the last months.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40] In addition, ZIFs derived SACs have excellent pore structure, which can effectively promote the transport of reactants and improve the catalytic performance. 41 Nevertheless, SACs derived from ZIFs have never been effectively explored in CTH of FF to FAL. Herein, we report Ni single-atoms supported on N-doped porous carbon (Ni-SAs/NC) catalyst, which was first ever utilized in CTH of FF to FAL.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, efficient catalytic systems, which were similar to the PtNi/SBA-15 catalytic system, were widely studied for selective C=O hydrogenation of FF/HMF. For example, Fan et al (2020) reported that 10 wt% Pt/C could catalyze 20% of FF conversion to FFA with 71.2% selectivity in tetrahydrofuran at 413 K under 2 MPa H 2 pressure. Lima et al (2017) reported that 44% selectivity to DHMF could be achieved over 10 wt% Pt/C at 373 K under 9 MPa H 2 pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reported catalytic systems for FF/HMF hydrogenation and hydrogenolysis, monometallic catalysts (e.g., Pt, Pd, Ni, Cu) were widely employed and investigated ( Sitthisa and Resasco, 2011 ; Chen et al, 2016 ; Guo et al, 2016 ; Lima et al, 2017 ; Fan et al, 2020 ; Yang et al, 2020 ). For example, Fan et al (2020) reported that FF hydrogenation over 10 wt% Pt/C catalyst could yield 14% FFA with 71.2% selectivity at 413 K. Sitthisa and Resasco (2011) reported that 69% conversion of FF and 68% selectivity to FFA could be achieved on 10 wt% Cu/SiO 2 at 503 K . However, monometallic catalyst with relatively high metal loading always accompanied with low metal dispersion, consequently resulting in the slow reaction rate, high reaction temperature and poor selectivity to FFA/DHMF.…”
Section: Introductionmentioning
confidence: 99%